2006
DOI: 10.1002/j.2050-0416.2006.tb00703.x
|View full text |Cite
|
Sign up to set email alerts
|

A Rapid Method for the Recovery, Quantification and Electrophoretic Analysis of Proteins from Beer

Abstract: A previously-developed method for protein recovery from wine has been applied to beer and beer foam samples. The method involves the complexation of proteins with dodecyl sulfate (added as sodium salts) and subsequently the insolubilization of the protein-detergent complexes by addition of potassium ions (added as KCl). The protocol allows preparation of proteins from a few hundred microliters of beverage in a few minutes. The precipitated proteins are free from interfering materials and are directly utilizabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…The concentration values were in accordance with those reported by other authors 7,27,29 . As expected the highest protein content was found in the wheat-unfiltered beer (i.e., Franziskaner and Franziskaner Dunkel).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The concentration values were in accordance with those reported by other authors 7,27,29 . As expected the highest protein content was found in the wheat-unfiltered beer (i.e., Franziskaner and Franziskaner Dunkel).…”
Section: Resultssupporting
confidence: 92%
“…The proteins KDS precipitation method 27 can be carried out on beverages using commonly available reagents and give well-resolved electrophoretic profiles. Recently we have reported that wine glycoproteins were not affected by the KDS method 12 , allowing their fractionated recovery by further acetone precipitation.…”
Section: Resultsmentioning
confidence: 99%
“…For these reasons, a combination of separation techniques with MS is required. This approach has been used many times for the analysis of barley protein extracts (e.g., Bak-Jensen et al, 2004;Celus et al, 2006;Chmelík et al, 2002;Finnie et al, 2006;Görg et al, 1992a,b;Hao et al, 2006;Hynek et al, 2006;Kanerva et al, 2005;Perrocheau et al, 2005;Rehulka et al, 2005;Savage et al, 2002;Veneri et al, 2006). Østergaard et al (2002) used a combination of 2D GE, MALDI-TOF MS and bioinformatics to characterize both mature barley seeds and five day micromalted seeds.…”
Section: Characterization Of Malt Proteins By Separation Techniques Cmentioning
confidence: 98%
“…A variety of procedures has been developed for beer protein analysis 1 . Electrophoretic and HPLC methods are extensively used in malt, wort and beer protein investigations 21,143,150 . Protein changes during malting, investigated by capillary electrophoresis, include a decrease of storage proteins, belonging to the prolamin and glutelin fractions, and an increase in some metabolically active proteins, belonging to the albumins and glutelins 90 .…”
Section: Beer Pathogenesis-related Proteins (Prs)mentioning
confidence: 99%